Advanced pharmacological uses of medicinal plants and natural products - Singh, Ajeet, 1991-; Singh, Padam, 1988-; Bithel, Navneet, 1963- (Medical Information Science Reference, an imprint of IGI Global, 2020)
"This book explores the pharmacological uses of medicinal plants and natural products"--Provided by publisher"--